The Ontological Difference in Heidegger's Thought: A Solution to the Puzzle of the Relationship between Being, entities, and Dasein in Being and Time - Nayerehsadat Mirmousa (Journal of Philosophical Investigations)
This paper examines three seemingly inconsistent passages in Martin Heidegger's Being and Time that pertain to the relationship between Being, entities, and Dasein. The apparent inconsistency arises from Heidegger's assertion that, on the one hand, entities are independent of Dasein, while on the other hand, Being is dependent on Dasein's understanding. This paper aims to resolve this apparent inconsistency by introducing and analyzing the ontological difference between Being and entities, which is a central concept in Heidegger's philosophy. By exploring Heidegger's critiques of traditional realist and idealist approaches and focusing on his analysis of Dasein as “being in the world” and relating to other entities, it is demonstrated that these three passages are entirely compatible within the framework of Heidegger's ontology. Since the mode of existence of Dasein as transcendence serves as the foundation of ontological difference, understanding all modes of being of entities (and not the entities themselves), including independence and dependence, is rooted in Dasein.